FoxO1 mediates insulin-dependent regulation of hepatic VLDL production in mice - Kamagate, Adama (American Society for Clinical Investigation, 2008)
Excessive production of triglyceride-rich VLDL is attributable to hypertriglyceridemia. VLDL production is facilitated by microsomal triglyceride transfer protein (MTP) in a rate-limiting step that is regulated by insulin. To characterize the underlying mechanism, we studied hepatic MTP regulation by forkhead box O1 (FoxO1), a transcription factor that plays a key role in hepatic insulin signaling. In HepG2 cells, MTP expression was induced by FoxO1 and inhibited by exposure to insulin. This effect correlated with the ability of FoxO1 to bind and stimulate MTP promoter activity. Deletion or mutation of the FoxO1 target site within the MTP promoter disabled FoxO1 binding and resulted in abolition of insulin-dependent regulation of MTP expression. We generated mice that expressed a constitutively active FoxO1 transgene and found that increased FoxO1 activity was associated with enhanced MTP expression, augmented VLDL production, and elevated plasma triglyceride levels. In contrast, RNAi-mediated silencing of hepatic FoxO1 was associated with reduced MTP and VLDL production in adult mice. Furthermore, we found that hepatic FoxO1 abundance and MTP production were increased in mice with abnormal triglyceride metabolism. These data suggest that FoxO1 mediates insulin regulation of MTP production and that augmented MTP levels may be a causative factor for VLDL overproduction and hypertriglyceridemia in diabetes.